2002
DOI: 10.1007/bf03179845
|View full text |Cite
|
Sign up to set email alerts
|

A maximal effort trial in obese women carrying the β2-adrenoceptor Gln27Glu polymorphism

Abstract: The aim of this study was to observe the relationship of the beta2-adrenoceptor (ADRB2) gene polymorphism Gln27Glu in a group of obese female subjects submitted to an acute physical activity test. Six Glu27/Glu27 obese women were compared with six Gln27/Gln27 obese women (coupled by age, BMI, waist circumference, percentage of fat mass and absence of smoking). These groups were selected after having genotyped 91 obese subjects (BMI>30 kg/m2, age 20-60). Polymerase chain reaction and restriction fragment length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…In men, the 27Glu allele has been associated with increased BMI, subcutaneous fat, elevated leptin and triglycerides levels and increased risk for abdominal obesity [27]. In an intervention study, our group has shown that women homozygotes for the 27Glu allele have impaired the exercise-stimulated lipolysis [23][24]. We also observed an effect modification (interaction) on obesity risk linked to the 27Glu polymorphism by recreational energy expenditure levels.…”
Section: Genes Encoding Factors Involved In Energy Expendituresupporting
confidence: 50%
See 1 more Smart Citation
“…In men, the 27Glu allele has been associated with increased BMI, subcutaneous fat, elevated leptin and triglycerides levels and increased risk for abdominal obesity [27]. In an intervention study, our group has shown that women homozygotes for the 27Glu allele have impaired the exercise-stimulated lipolysis [23][24]. We also observed an effect modification (interaction) on obesity risk linked to the 27Glu polymorphism by recreational energy expenditure levels.…”
Section: Genes Encoding Factors Involved In Energy Expendituresupporting
confidence: 50%
“…The peripheral transmission of central commands to the fat stores is mediated by sympathetic nervous system. The β-adrenoceptor gene family contains classical obesity candidate genes for its role in the regulation of energy expenditure [3,[23][24][25][26][27][28][29][30][31][32].…”
Section: Genes Encoding Factors Involved In Energy Expenditurementioning
confidence: 99%
“…In addition, publication bias towards positive results may overestimate the strength of an association. Conversely, true candidate gene effects may be missed if they are modulated by the presence of gene-environment interactions (such as those reported to occur between exercise and polymorphisms in the β 2 -adrenoceptor gene; Macho-Azcarate et al, 2002) or have effects specific to certain ethnic groups or sexes.…”
Section: Candidate Genes Based On Physiological Functionmentioning
confidence: 99%
“…(Email: chikuni@affrc.go.jp) coding region of human ADRB genes, each of them involving amino acid substitution, and they have been investigated as candidates for obesity genes. Numerous studies into ADRB2 polymorphisms in different human groups have been undertaken, and the results suggest the risk of ADRB2 polymorphisms in obesity (Large et al 1997;Ellsworth et al 2002;Kim et al 2002;Macho-Azcarate et al 2002;Garenc et al 2003;Martinez et al 2003;Park et al 2005) and ADRB2 association with fat metabolism (Carlsson et al 2001;Petrone et al 2006).…”
Section: Introductionmentioning
confidence: 99%